Kobiety w polityce : sfera publiczna (Wydawnictwo Księgarnia Akademicka, 2020)
WOMEN IN POLITICS. THE PUBLIC SPHERE Culture, which is the basis of individual and collective mentality, has power to form and re-form human behaviour, ambitions, actions, plans, etc. The cultural dimension is therefore highly important for the issues presented in this publication. Mentality consent to the presence of women in politics as active agents, and not only passive (absent) actors, can and does happen precisely through cultural changes. In this case, projects promoting gender equality, equal access of women and men to material and symbolic goods, such as work and prestige, play a fundamental role. Also in the field of education, it is vital to encourage children and young adults, regardless of gender, to become involved in political life, without stigmatizing, discriminating against or perpetuating stereotypical thinking about women. The topic of women’s participation in politics still remains a vivid issue, calling for inclusion in the general public discourse and general social awareness and, above all, everyday practice. Let this publication be an invitation to do so.